The relevance of family caregiver support to the resilience and spirituality of advanced breast cancer patients through the perspective of religious psychology - Sihombing, Sarah Natasya; Ranimpi, Yulius Yusak; Harisantoso, Imanuel Teguh (http://dharmais.co.id/, 2025)
Introduction: Based on the type of disease, breast cancer is the most common. Individuals who suffer from this disease will experience several changes, including physiological, psychological, social, and spiritual aspects. In the psychological aspect, it can be seen from changes in attitude and behavior, such as depression, anxiety, and emotional instability. Regarding this matter, breast cancer patients who are already in the advanced stage and need help and support from family members to have spirituality and resilience to live well. The research aims to describe and analyze the relevance of family caregiver support for the resilience and spirituality of advanced breast cancer sufferers from the perspective of religious psychology.Method: This research uses qualitative research methods with a case study research design. The data collection technique used in this research was by interviewing the participants involved, namely two women aged 59 years and 60 years who had advanced-stage breast cancer and two family caregivers.Results: The results of the research stated that the support of a family caregiver who always provides support, both spiritually and emotionally, has a great influence on the spirituality and resilience of breast cancer sufferers. This can be seen from the lower level of pain in breast cancer sufferers who have strong resilience and a better ability to overcome the problems faced by breast cancer sufferers who have high spirituality.Conclusion: Support from family caregivers emotionally, practically, and financially provides encouragement and comfort for patients with advanced breast cancer, which reduces anxiety in patients and increases the resilience and spirituality of patients. The resilience of patients with advanced breast cancer can be formed because there is reinforcement that fosters hope for survival and fight from family caregivers.